(untitled) (Revista de Ciências Agroveterinárias, 2019)
Our objective was to understand the C. guazumifolia reproductive and vegetative cycles , monitoring its phenological events and correlating them to the climatic data of the studied region. Two evaluation methods were used, the activity index and the intensity index (Fournier index). The flowering phenophase occurred between the months of October and December, and from March to April, with Fournier peaks of intensity in November. The fruiting occurred from December to April, being December the most intense. The species presented the biggest foliar fall period between March and September, with intensity peak in August, and the budding presented a peak in September. It was observed a positive correlation between the climatic variables of maximum and minimum monthly temperatures to fruiting, and negative correlation between the climatic variables of maximum and medium monthly temperatures to foliar fall.